2014
DOI: 10.1177/0887403414521461
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Legal and Non-Legal Factors Associated With Exoneration for Wrongful Conviction

Abstract: This study provides an exploratory quantitative examination of wrongful criminal conviction. Certain legal factors and perhaps some non-legal factors are related to wrongful conviction. Using data pertaining to all known exonerations in the United States from 1989 to 2012, we explore the extent to which deoxyribonucleic acid (DNA) testing and/or race of a convicted innocent are related to that person's exoneration. Controlling for race, the availability of DNA testing increases the likelihood of exoneration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…death sentence cases, Gross and O'Brien, 2008;Gross et al, 2014) or -more recentlyutilizing Michigan Law School's "National registry of exonerations" (e.g. Gross and Shaffer, 2012;Olney and Bonn, 2014).…”
Section: Using Appeal Results As a Proxy For Judicial Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…death sentence cases, Gross and O'Brien, 2008;Gross et al, 2014) or -more recentlyutilizing Michigan Law School's "National registry of exonerations" (e.g. Gross and Shaffer, 2012;Olney and Bonn, 2014).…”
Section: Using Appeal Results As a Proxy For Judicial Errorsmentioning
confidence: 99%
“…For example, most exonerations rely on DNA evidence, which might correspond mainly to identity errors, where the actual culprit left DNA at the scene. Similarly, exonerations might include only defendants with sufficient resources for access to representation (Olney and Bonn, 2014). This paper takes a different approach, by utilizing aggregated appeal results as a proxy for judicial errors and their correction.…”
Section: Using Appeal Results As a Proxy For Judicial Errorsmentioning
confidence: 99%
“…Biometric evidence in particular suffers from this problem of misplaced and excessive faith in technology and its perceived infallibility (Schklar and Diamond, 1999)-for example, the use of DNA evidence in otherwise weak, circumstantial criminal cases significantly increases the likelihood of conviction (Dartnall and Goodman-Delahunty, 2006). In reality, the quality of biometric evidence is far from perfect [and sometimes even faked (Giannelli, 1997)] and can lead to convictions of innocent people in alarming numbers of cases (Naughton and Tan, 2011), few of which are successfully reviewed and overturned (although the positive role DNA evidence can play in overturning wrongful convictions also has to be mentioned (Olney and Bonn, 2015).…”
Section: Evaluation and Assessmentmentioning
confidence: 99%
“…Empirical evidence indicates that DNA testing is an important influencing factor in exonerations (see Gross et al, 2017; Krieger, 2011; Laporte, 2017; Olney & Bonn, 2015; Rafail & Mahoney, 2019; E. Smith & Hattery, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smith & Hattery, 2011), 1 the availability of DNA has been found to speed up the exoneration process (Rafail & Mahoney, 2019). Olney and Bonn (2015) examined NRE data from 1989 to 2012 and found that DNA testing increased the odds of exoneration for those wrongfully convicted of murder and sexual assault. Based on NRE data (1989–2015), and supplemented with Census and county election data, they also found that having a DNA-based defense increased the likelihood of exoneration by 456% (Rafail & Mahoney, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%